2005
DOI: 10.1002/bin.200
|View full text |Cite
|
Sign up to set email alerts
|

The analysis and treatment of vocal stereotypy in a child with autism

Abstract: This study examined procedures for the assessment and treatment of automatically reinforced vocal stereotypy of a 6-year-old girl with autism. Stimulus assessments were conducted to identify toys that were correlated with higher rates of vocal stereotypy and toys that were not. A concurrent operants assessment identified preferred stimuli (toys that produced auditory stimulation), which were then used as reinforcers for the non-occurrence of vocal stereotypy. A reversal design was used to compare the effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
84
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(88 citation statements)
references
References 28 publications
4
84
0
Order By: Relevance
“…This is similar to the findings of Taylor et al (2005), which imply that the sounds produced by stereotypic vocalizations are the operative sensory consequence that maintains stereotypy. However, the vibration produced by engaging in the vocalizations cannot be ruled out as a reinforcer.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This is similar to the findings of Taylor et al (2005), which imply that the sounds produced by stereotypic vocalizations are the operative sensory consequence that maintains stereotypy. However, the vibration produced by engaging in the vocalizations cannot be ruled out as a reinforcer.…”
Section: Discussionsupporting
confidence: 87%
“…It should be noted that access to dissimilar forms of sensory stimulation can also produce lower levels of stereotypy (e.g., Ahearn, Clark, DeBar, & Florentino, 2005;Vollmer, Marcus, & LeBlanc, 1994). Furthermore, Taylor et al (2005) found that providing contingent access to matched stimulation through a negative punishment contingency (i.e., differential reinforcement of other behavior) produced a low level of vocal stereotypy for a child with autism, but response-independent access to that stimulation was ineffective. Such differential reinforcement is also not always successful in decreasing stereotypic responding (e.g., Fellner, Laroche, & Sulzer-Azaroff, 1984).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Functional analysis of vocal stereotypy in individuals with autism typically resulted in undifferentiated patterns between the behavior and the social environment in a majority of the reported studies (Ahearn et al, 2007;Graff, Lineman, Libby, & Ahearn, 1999;Kennedy et al, 2000;Taylor, Hoch, & Weissman, 2005). Although the majority of such studies concluded that the behaviors were maintained by sensoryrelated reinforcement, Kennedy and colleagues cautioned that the causes of stereotypy in individuals with are complex, and that it is less important to presume association between response and behavioral function for treatment purposes.…”
Section: Discussionmentioning
confidence: 91%
“…Beside yield losses, excessive nitrogen treatments may also result in various environmental problems over agricultural fields (Grant, 2006). Among the inputs to be provided to improve plant yields, fertilizers constitute about 58% of such inputs (Taylor et al, 2005). Nitrogen is the mostly observed insufficiency in plant production, but it is an essential and yield-improving plant nutrient.…”
Section: Introductionmentioning
confidence: 99%